Preaching Spanish Nationalism across the Hispanic Atlantic, 1759-1823 - Eastman, Scott, 1971- (Book collections on Project MUSE., 2012)
In this debut work, Scott Eastman tackles the thorny issue of nationalism in the eighteenth- and nineteenth-century Spanish Atlantic Empire. Preaching Spanish Nationalism across the Hispanic Atlantic challenges the idea that nationalism was constructed out of the ashes of confessional society. Rather, the tenets of Roman Catholicism and the ideals of Enlightenment worked together to lay the basis for a ômixed modernityö within the territories of the Spanish monarchy. Drawing on sermons, catechisms, political pamphlets, and newspapers, Eastman demonstrates how religion and tradition were bound.